The impact of infrastructure upon the spiritual culture of the city in the industrial era: philosophical analysis - Кравченко, О. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article made a philosophical study of the impact of infrastructure on the spiritual culture of the city in the industrial era.